2018
DOI: 10.3847/1538-4357/aacdfe
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic-Ray Short Burst Observed with the Global Muon Detector Network (GMDN) on 2015 June 22

Abstract: We analyze the short cosmic-ray intensity increase ("cosmic-ray burst": CRB) on 2015 June 22 utilizing a global network of muon detectors and derive the global anisotropy of cosmic-ray intensity and the density (i.e., the omnidirectional intensity) with 10 minute time resolution. We find that the CRB was caused by a local density maximum and an enhanced anisotropy of cosmic rays, both of which appeared in association with Earth's crossing of the heliospheric current sheet (HCS). This enhanced anisotropy was no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…A similar idea was also presented by Mohanty et al (2016) to interpret the "cosmic-ray short burst" observed by a muon detector in June 2015. Based on calculations of cosmic-ray trajectory in the latest model of geomagnetic field, however, analyses of the same event by Munakata et al (2018) showed that the reductions of P c and the magnetic deflection of cosmic-ray orbits are not enough to cause the observed intensity increase of 60 GeV cosmic rays monitored by the GMDN, because the GMDN only has a small response to cosmic rays with rigidities around P c . They attributed the burst to enhancements of I 0 (t) and ξ(t) outside the magnetosphere caused by Earth's crossing the heliospheric current sheet (Munakata et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A similar idea was also presented by Mohanty et al (2016) to interpret the "cosmic-ray short burst" observed by a muon detector in June 2015. Based on calculations of cosmic-ray trajectory in the latest model of geomagnetic field, however, analyses of the same event by Munakata et al (2018) showed that the reductions of P c and the magnetic deflection of cosmic-ray orbits are not enough to cause the observed intensity increase of 60 GeV cosmic rays monitored by the GMDN, because the GMDN only has a small response to cosmic rays with rigidities around P c . They attributed the burst to enhancements of I 0 (t) and ξ(t) outside the magnetosphere caused by Earth's crossing the heliospheric current sheet (Munakata et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, these effects can lead to a short enhancement or burst of the CR count rate on the background of the main FD observed at some neutron monitors (NMs). Several such events recorded during Cycle 24 are analyzed in the recent papers by Evenson et al (2017), Gil et al (2018), Munakata et al (2018), Samara et al (2018). Even those CR bursts that stand out well at the FD recovery phase do not usually reach the pre-event count rate level.…”
Section: Introductionmentioning
confidence: 99%
“…A small local maximum is seen in I 0 (t) at around 10:00 UT of 25 August being superposed on the gradual decrease in the sheath period. We think that this is probably due to the discontinuity recorded in the IMF magnitude and longitude seen in Figures 1c-d, because such a local increase of I 0 (t) is often observed by the GMDN at the IMF discontinuity (Munakata et al, 2018).…”
Section: Resultsmentioning
confidence: 85%